2015
DOI: 10.1007/s40980-015-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Demographic and Health Survey Point Displacements on Distance-Based Analyses

Abstract: We evaluate the impacts of random spatial displacements on analyses that involve distance measures from displaced Demographic and Health Survey (DHS) clusters to nearest ancillary point or line features, such as health resources or roads. We use simulation and case studies to address the effects of this introduced error, and propose use of regression calibration (RC) to reduce its impact. Results suggest that RC outperforms analyses involving naive distance-based covariate assignments by reducing the bias and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The Global Forest Change data are downloadable as tiff panels; we downloaded those panels covering the spatial extent of our 15 study countries in SSA (Hansen et al, 2013). The georeferenced DHS cluster locations are randomly displaced in order to protect the confidentiality of the survey respondents (Warren et al, 2016). The large majority (99%) of the locations are displaced by 0-5 km, with a remaining 1% of rural clusters displaced to a maximum of 10 km (Measure DHS/ICF International, 2012).…”
Section: Independent Variablementioning
confidence: 99%
“…The Global Forest Change data are downloadable as tiff panels; we downloaded those panels covering the spatial extent of our 15 study countries in SSA (Hansen et al, 2013). The georeferenced DHS cluster locations are randomly displaced in order to protect the confidentiality of the survey respondents (Warren et al, 2016). The large majority (99%) of the locations are displaced by 0-5 km, with a remaining 1% of rural clusters displaced to a maximum of 10 km (Measure DHS/ICF International, 2012).…”
Section: Independent Variablementioning
confidence: 99%
“…The preliminary analysis presented here has been motivated by concern with facilitating socio-ecological research while preserving the confidentiality of social science survey respondents. Several studies have emerged over the past several years examining the potential error introduced by geomasking techniques, but most such research has examined error with regard to the creation of distance-based measures such as distance to health clinic (e.g., Warren et al, 2016). Results suggest that the creation of these distance-based covariates can yield consequential measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although it can be shown that the expected measurement error in distances has positive mean and is bounded when measuring the distance to a single fixed point (Elkies et al ., ), when measuring distance to the nearest of a set of facilities, it is possible that the ‘nearest’ facility may change when noise is added to the household location, and the distribution of the errors that are induced depends on the precise locations of the facilities. If we assume that the distributions of actual distances and of the measurement errors in distances that are induced by using perturbed locations are independent and normally distributed, then we can apply standard regression calibration methods (Warren et al ., ). However, none of these assumptions are true (Arbia et al ., ; Elkies et al ., ), which makes this method unlikely to solve the problem.…”
Section: Introductionmentioning
confidence: 97%